New student admission information system design with payment gateway - Alfitra Oktavian; Uce Indahyanti; Ika Ratna Indra Astutik (Jurnal Mantik, 2023)
Regarding the rapid phase of technological progress in all fields, as well as the pattern of people's lives that have been relatively advanced. The purpose of this research is to design a payment gateway-based student admission system at SMP Muhammadiyah 3 Waru using the waterfall method. Web-based information systems can be used as a means of improving information in the education department. In the existing research on the information system for new student admissions, payment processing is carried out manually by paying on the spot or transferring to the school accounts. It is required to confirm payments and utilize SMS gateways as an information forwarder to information. This system delivers complete information such as how to register, test, and payment gateway-based methods. The results obtained by all service menus on the system have been running well.